Benzoxazole-terminated liquid crystals with high birefringence and large dielectric anisotropy. Issue 9 (14th July 2020) - Hu, Kun; Weng, Qiang; Chen, Ran; Li, Jian; Shi, Dingqian; Chen, Pei; Gao, Aiai; Chen, Xinbing; An, Zhongwei
ABSTRACT: Six benzoxazole-terminated mesogenic compounds with fluoro substituent at different positions were prepared and their properties investigated. The compounds give a high birefringence (Δ n ~ 0.45) and a large-dielectric anisotropy (Δ ε ~ 26), indicating a possible application in liquid-crystal mixture as a dopant to enhance performance of the host mixture. In accordance with conventional high Δ n liquid crystals containing triple carbon-carbon bonds, lateral fluoro substituents and terminal groups can alter the Δ n and Δ ε of benzoxazole-terminated liquid crystals. Meanwhile, some parameters such as dipole moment, polarisability, dihedral angles are calculated with density functional theory (DFT) methods to relate to the experimental Δ n and Δ ε . It is noted that the introduction of the benzoxazole unit is an effective method to enhance Δ n and Δ ε values of the rodlike molecule, this is ascribed to its π-conjugated benzene-fused heterocycle and large dipole moment. Graphical Abstract: uf0001